A Novel Van der Woude Syndrome-Causing IRF6 Variant Is Subject to Incomplete Non-sense-Mediated mRNA Decay Affecting the Phenotype of Keratinocytes - Degen, Martin; Girousi, Eleftheria; Feldmann, Julia; Parisi, Ludovica; La Scala, Giorgio C.; Schnyder, Isabelle; Schaller, André; Katsaros, Christos (Frontiers in Cell and Developmental Biology, 2020)
Van der Woude syndrome (VWS) is a genetic syndrome that leads to typical phenotypic traits, including lower lip pits and cleft lip/palate (CLP). The majority of VWS-affected patients harbor a pathogenic variant in the gene encoding for the transcription factor interferon regulatory factor 6 (IRF6), a crucial regulator of orofacial development, epidermal differentiation and tissue repair. However, most of the underlying mechanisms leading from pathogenic IRF6 gene variants to phenotypes observed in VWS remain poorly understood and elusive. The availability of one VWS individual within our cohort of CLP patients allowed us to identify a novel VWS-causing IRF6 variant and to functionally characterize it. Using VWS patient-derived keratinocytes, we reveal that most of the mutated IRF6_VWS transcripts are subject to a nonsense-mediated mRNA decay mechanism, resulting in IRF6 haploinsufficiency. While moderate levels of IRF6_VWS remain detectable in the VWS keratinocytes, our data illustrate that the IRF6_VWS protein, which lacks part of its protein-binding domain and its whole C-terminus, is noticeably less stable than its wild-type counterpart. Still, it maintains transcription factor function. As we report and characterize a so far undescribed VWS-causing IRF6 variant, our results shed light on the physiological as well as pathological role of IRF6 in keratinocytes. This acquired knowledge is essential for a better understanding of the molecular mechanisms leading to VWS and CLP.